Earthquakes economic costs through rank-size laws. (14th August 2017) - Ficcadenti, Valerio; Cerqueti, Roy
Abstract: This paper is devoted to assessing the presence of some regularities in the magnitudes of the earthquakes in Italy between January 24 t h, 2016 and January 24 t h, 2017, and to propose an earthquakes cost indicator. The considered data includes the catastrophic events in Amatrice and in the Marche region. To our purpose, we implement two typologies of rank-size analysis: the classical Zipf–Mandelbrot law and the so-called universal law proposed by Ausloos and Cerqueti (2016 PLoS One 11 e0166011). The proposed generic measure of the economic impact of earthquakes moves from the assumption of the existence of a cause-effect relation between earthquakes magnitudes and economic costs. At this aim, we hypothesize that such a relation can be formalized in a functional way to show how infrastructure resistance affects the cost. Results allow us to clarify the impact of an earthquake on the social context and might serve to strengthen the struggle against the dramatic outcomes of such natural phenomena.